COMPARISON OF NON-INVASIVE FOLLOW-UP TESTING IN PATIENTS AFTER PERCUTANEOUS CORONARY INTERVENTION WITH DRUG-ELUTING STENT IMPLANTATION - AJMAL , L; KHAN , AA; AJMAL , MA; ULLAH , H (Biological and Clinical Sciences Research Journal, 2023)
Percutaneous coronary intervention (PCI) is a common procedure used to treat obstructive coronary artery disease (CAD). The aim of this retrospective cohort study, conducted at the Armed Forces Institute of Cardiology from January 2019 to December 2021, was to compare non-invasive follow-up testing in patients who underwent PCI with drug-eluting stent (DES) implantation. The study included 210 patients who underwent PCI with DES implantation at AFIC during the specified period. Researchers extracted patient data, including demographic information, clinical characteristics, PCI procedural details, and baseline comorbidities from electronic medical records. They also recorded additional data on the type of DES used, lesion characteristics, and stent dimensions. Of the 210 patients included in the study, the mean age was 62 years, with a range of 45 to 78 years. The data comprised 65% males and 35% females. The most common comorbidities were hypertension (80%), diabetes mellitus (60%), and dyslipidemia (45%). 30% of patients had a family history of coronary artery disease. During the follow-up period, restenosis was detected in 18% of patients, while stent thrombosis occurred in 7% of cases. The incidence of major adverse cardiac events (MACE) was 25%, with myocardial infarction accounting for 12%, target lesion revascularization for 10%, and cardiac mortality for 3% of MACE cases. Based on the results, the study highlights the importance of non-invasive follow-up testing in patients who have undergone PCI with DES implantation. These modalities provide diagnostic accuracy, prognostic value, and cost-effectiveness, contributing to a more comprehensive understanding of their role in post-PCI care.